Direct online monitoring and control of chemical reactions using dielectric spectroscopy - Kalamiotis, Alexis (2020)
Over the last decades, the increasing demand for both the production of biobased products and the need for more sustainable material synthesis processes led to the development of novel techniques such as the Nitroxide Mediated Polymerization (NMP), Catalytic Chain Transfer Polymerisation (CCTP), and Ring-Opening Polymerisation (ROP). However, the commercial development of those techniques has been limited, with a key issue being the need to determine how far a particular reaction has progressed in order to continue to the next stage of the process (e.g., addition of other reactants) or terminate the reaction when the target conversion has been reached. Dielectric spectroscopy has been considered a promising technique for ‘in-situ’ monitoring since it is a non-invasive technique which can be applied to most industrial reactors. The aims of this research were to investigate the use of dielectric spectroscopy for the ‘in-situ’ monitoring of chemical reactions at microwave frequencies and relate the dielectric properties with key reaction features such as the molecular weight and the level of conversion that has been achieved. The thesis presents a detailed study of the tin octanoate mediated ROP of ε-caprolactone, and the para toluene sulfonic acid catalysed hydrolysis of sorbitol to sorbitan and isosorbide. Additionally, dielectric spectroscopy was utilised to differentiate the polymer architecture and molecular weight of Styrene–divinylbenzene copolymers synthesised by CCTP and NMP. An open-ended coaxial line sensor was placed directly into the reaction medium and used to measure the dielectric properties of the mixture both “in-situ” and with time. A swept signal (0.5 GHz–20 GHz) was then transmitted from a Vector Network Analyser (VNA), through the open-ended coaxial line, into the sample. Depending on the complex permittivity of the sample, a portion of that signal was reflected to the VNA and the reflection coefficient of the sample was used to calculate the complex permittivity. In addition to the measurements obtained by the sensor, samples of the medium were extracted at various time points for off-line analysis, using Gel Permeation Chromatography and Nuclear Magnetic Resonance spectroscopy to confirm key reaction features, e.g., molecular weight and the level of conversion that had been achieved. The results demonstrated that in case of ε-caprolactone polymerisation and sorbitol dehydration the dielectric property values exhibited by the reaction medium could be correlated to both the progress of the reaction and the structure of the final product. Thus, the experimental data allowed the construction of a calibration curve which could be used to predict the level of conversion that has been achieved. The use of dielectric data also permitted the identification of key reaction parameters, such as the optimum point of termination for the reaction. Furthermore, the analysis of the dielectric data over a wide frequency spectrum enabled the identification of the most suitable frequencies for the practical operation of the sensor, in terms of linearity and sensitivity. This study has demonstrated a method to determine the product properties or conversion during the reaction progress based on the real-time measurement of the dielectric properties during the ε-caprolactone polymerisation and sorbitol dehydration. This work provides a basis for developing process control strategies based on observing the change in the dielectric properties which can be applied to commercial manufacturing. The proposed method could improve product quality (e.g., by terminating the reaction when the target conversion has been reached batch to batch repeatability can be improved) and reduce the production cost of materials, e.g., by optimising the amount of time that the reaction is kept at the required temperature, energy usage and waste generation can be minimised).